Nowtopia : how pirate programmers, outlaw bicyclists, and vacant-lot gardeners are inventing the future today - Carlsson, Chris, 1957- (Edinburgh : Oakland : AK Press, 2008)
"Nowtopia" uncovers the resistance of a slowly recomposing working class in America. Rarely defining themselves by what they do for a living, people from all walks of life are doing incredible amounts of labor in their "non-work" time, creating immediate practical improvements in daily life. The social networks they create, and the practical experience of cooperating outside of economic regulation, become a breeding ground for new strategies to confront the commodification to which capitalism reduces us all.
Includes bibliographical references (p. [253]-271).
Keywords: Quality of life; Alternative lifestyles; Social networks; Work and family; Primera Jornada de Catalogación.; Calidad de vida; Trabajo y familia